2016
DOI: 10.1177/0956797616645673
|View full text |Cite
|
Sign up to set email alerts
|

The Power of the Like in Adolescence

Abstract: We investigated a unique way in which adolescent peer influence occurs on social media. We developed a novel fMRI paradigm to simulate the popular social photo-sharing tool Instagram, and measured adolescents’ behavioral and neural responses to “Likes,” a quantifiable form of social endorsement and potential source of peer influence. Adolescents underwent fMRI while viewing photographs ostensibly submitted to Instagram. Adolescents were more likely to Like photos depicted with many Likes and refrain from Likin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
151
1
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 385 publications
(203 citation statements)
references
References 31 publications
10
151
1
3
Order By: Relevance
“…In order to account for this confound, we accounted for the popularity of images in our model; thus, the Like > Next contrast represents brain responses related to this contrast over and above the effects of popularity. Similarly, results of our ‘Getting Likes’ contrast may in part reflect the neural correlates of giving Likes to ‘oneself’, since participants were more likely to select Like on their own photographs when these images appeared popular (Sherman et al , 2016, 2017), although they also frequently Liked their own unpopular images.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…In order to account for this confound, we accounted for the popularity of images in our model; thus, the Like > Next contrast represents brain responses related to this contrast over and above the effects of popularity. Similarly, results of our ‘Getting Likes’ contrast may in part reflect the neural correlates of giving Likes to ‘oneself’, since participants were more likely to select Like on their own photographs when these images appeared popular (Sherman et al , 2016, 2017), although they also frequently Liked their own unpopular images.…”
Section: Discussionmentioning
confidence: 73%
“…Participants gave written consent (or, for individuals under 18, written assent and parental consent), and were fully debriefed and compensated monetarily according to study procedures approved by the Institutional Review Board of the University of California, Los Angeles. These participants have been previously reported upon (Sherman et al , 2016, 2017). …”
Section: Methodsmentioning
confidence: 99%
“…Given the challenges of self-report data in regard to social media use, a number of other methods should be employed as well, with preliminary work showing promise in the use of novel methods, such as observational coding of adolescent social media pages (e.g., Moreno et al 2012; Underwood et al 2013), ecological momentary assessment (e.g., Jelenchick et al 2013), media diaries (e.g., Gross 2004), and guided “tours” of social media pages (e.g., Salimkhan et al 2010). In addition, the application of fMRI techniques to examining adolescent social media use will add a level of complexity and greater nuance to our understanding of these processes, as has been shown in preliminary work (e.g., Sherman et al 2016). Measures of physiological activity, including heart rate and blood pressure, have also recently been applied to examining adults’ experiences of stress when separated from their cell phones (Clayton et al 2015); similar measures may provide insight into adolescents’ physiological response to social media.…”
Section: Building On the Transformation Framework: Methodological Conmentioning
confidence: 98%
“…Insight into the mechanisms by which this may occur is found in the first study to apply an fMRI paradigm to adolescent social media use. Through a simulation of the social media site Instagram, Sherman et al (2016) found that when adolescents viewed photographs with higher numbers of likes, they were influenced to “like” those photographs as well. When viewing photographs with more likes, compared to fewer likes, adolescents showed greater activation in the precuneus, medial prefrontal cortex, and hippocampus, which are areas relevant to social cognition and social memories, as well as the inferior frontal gyrus, which is important for imitation.…”
Section: Peer Influencementioning
confidence: 99%
“…They are of special interest because these same areas are often implicated in addictive behaviors (Meshi, Tamir, & Heekeren, 2015). Sherman, Payton, Hernandez, Greenfield, & Dapretto (2016) studied adolescent peer influence by simulating the social photo-sharing platform Instagram. They measured adolescents' behavioral and neural responses to "likes" while they were undergoing fMRI and simultaneously viewing photographs they believed had been submitted to Instagram.…”
Section: Brain Consequences Of the New Social Mediamentioning
confidence: 99%